Georgian Economy retrospective: from the Soviet Planning time to the transition - David Aslanishvili (Foundations and Trends in Research, 2024)
An article has described the transition of Soviet Type planned centralized economic system to market economy, its obstacles, view, and reforms. A complexity of the situation and a speedy implementation of reforms call for a thorough analysis of Georgia's social and economic stances and a research into the causes and peculiarities of the crisis, on the one hand, and a formation of an effective macro – economic policy, on the other. The objective of the research is an analysis of Georgia's social and economic stances and a subsequent definition of individual directions of macro – economic policy for the foreseeable future.